2015 Global hunger index: Armed conflict and the challenge of hunger - von Grebmer, Klaus; Bernstein, Jill; de Waal, Alex; Prasai, Nilam; Yin, Sandra; Yohannes, Yisehac (International Food Policy Research Institute, 2015)
The developing world has made progress in reducing hunger since 2000. The 2015 Global Hunger Index (GHI) shows that the level of hunger in developing countries as a group has fallen by 27 percent. Yet the state of hunger in the world remains serious. This marks the tenth year that IFPRI has assessed global hunger using this multidimensional measure. This report’s GHI scores are based on a new, improved formula that replaces the child underweight indicator of previous years with child stunting and child wasting. This change reflects the latest thinking on the most suitable indicators for child undernutrition, one of three dimensions of hunger reflected in the GHI formula. Across regions and countries, GHI scores vary considerably. Regionally, the highest GHI scores, and therefore the highest hunger levels, are still found in Africa south of the Sahara and South Asia. Despite achieving the largest absolute improvements since 2000, these two regions still suffer from serious levels of hunger. Levels of hunger are alarming or serious in 52 countries. Most of the eight countries with alarming GHI scores are in Africa south of the Sahara. While no countries are classified in the extremely alarming category this year, this high level of hunger could still exist. Due to insufficient data, 2015 GHI scores could not be calculated for places that recently suffered from high levels of hunger, including Burundi, Comoros, Democratic Republic of the Congo, Eritrea, Somalia, South Sudan, and Sudan.